Aprimoramento da metodologia de Hansen utilizando microscopia óptica com controle de temperatura - Souza, Bruno Dias De (2017)
Charles Hansen proposed to describe the solubility in three parameters: a dispersion, a polar and another of hydrogen bonding parameters, which can be graphically obtained from the solubility parameters of other substances. The solvents parameters, assumed as Cartesian coordinates, are analyzed in a computational function adjustment algorithm and a solubility sphere that encompasses all solvents that solubilize the solute. Variations in temperature of the system do not significantly affect the values of the solubility parameters, but an increase in temperature can increase the solubilized amount of a solute. Consequently, solvents previously considered bad may become good solvents. The aim of this work was to evaluate the Hansen solubility parameters by means of its methodology in 20 different pure solvents and 10 solvent mixtures, improved with the use of optical microscopy with temperature control. The purpose of this modification was to determine the saturation temperature of the solute in different solvents and to find an optimum working temperature level to obtain similar amounts of good and bad solvents, which is a condition that favors the achievement of more precise parameters and solubility radius. The results obtained by the microscopy (dynamic tests) have presented great similarity with the traditional methodology (static tests). Both tests found that at 22 °C, balanced amounts of good and bad solvents are obtained for palmitic acid. For stearic acid, it was found this condition at 28 °C for static tests and 31 °C for dynamic tests. It could also be noticed that it is possible to find a temperature range in which the amounts of good and bad solvents are similar. It also allowed an adjustment and obtaining of parameters of more precise solubility. It was possible to verify the increase in solubility radius and decrease in the number of anomalies with increasing temperature. From the obtained results, it was possible to affirm that the suggested improvement can replace the tests proposed by the Hansen methodology, carrying time gains from analysis and accuracy of the adjustment performed in the computational stage. Therefore, it is suggested that Hansen methodology be performed at 31 °C for stearic acid and 22 °C for palmitic acid.